2023
DOI: 10.1002/pan3.10546
|View full text |Cite
|
Sign up to set email alerts
|

Why reconnect to nature in times of crisis? Ecosystem contributions to the resilience and well‐being of people going back to the land in Greece

K. Benessaiah,
K. M. Chan

Abstract: Multiple crises, including climate change, ecosystem degradation, economic, political and social upheavals, severely impact people's well‐being. Ecosystem services (or nature's contributions to people) play a key role during crisis that needs to be further elucidated. Most research focusses on the material benefits that ecosystems provide in times of crisis, paying less attention to intertwined intangible, nonmaterial dimensions. Yet, these intangible ecosystem benefits are often crucial for people's resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 134 publications
0
0
0
Order By: Relevance
“…Previous literature has shown that both the quantity and quality of nature contact (and the extent to which the contact includes active nature engagement) may enhance the nature connectedness of both children and adults (Barrable & Booth, 2020b;Sheffield et al, 2022). The role that connection to nature plays in promoting wellbeing might be particularly important for Greek adults given the recent history of economic crisis within the country and the way that going 'back to the land' supported some people navigating that tumultuous period (Benessaiah & Chan, 2023). Future research with Greek samples should investigate if those adults who are more connected to nature also experience greater well-being; if that is the case, subsequent work should then explore how childhood nature activities can be promoted more effectively in Greece to support life-long relationships with nature and improved wellbeing.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature has shown that both the quantity and quality of nature contact (and the extent to which the contact includes active nature engagement) may enhance the nature connectedness of both children and adults (Barrable & Booth, 2020b;Sheffield et al, 2022). The role that connection to nature plays in promoting wellbeing might be particularly important for Greek adults given the recent history of economic crisis within the country and the way that going 'back to the land' supported some people navigating that tumultuous period (Benessaiah & Chan, 2023). Future research with Greek samples should investigate if those adults who are more connected to nature also experience greater well-being; if that is the case, subsequent work should then explore how childhood nature activities can be promoted more effectively in Greece to support life-long relationships with nature and improved wellbeing.…”
Section: Main Findingsmentioning
confidence: 99%
“…This may be for a variety of reasons, including seeing Greece as a representative of newly urbanised countries, as well as within the broader recent socio-economic context of Southern Europe, within which countries have experienced a rapid and progressive delocalisation of population over the last 50 years as well as pressing economic downturn (Vinci et al, 2022). However, it is important to note that previous research on Greece has reported fluid urban-rural linkages, and that in the aftermath of the 2008 economic crisis in Greece, revitalised relationships with nature brought along a range of benefits and implications for how people used nature to cope with crises (Benessaiah & Chan, 2023). Thus, the present study draws upon this unique context by asking Greek-speaking adult participants to reflect on their childhood experiences in nature, which took place during the pre-economic crisis, and their adulthood experiences and connections, most of which will have taken place during or after the economic crisis, to understand the links through a longitudinal lens.…”
Section: Introductionmentioning
confidence: 99%